Implementation of Islamic Values of Rahmatan lil 'Alamin in Multicultural Life in Iraq - Mohammed Abdu Rehany (CV Edujavare Publishing, 2024)
The concept of Rahmatan lil ‘Alamin represents one of the fundamental principles of Islam emphasizing mercy, compassion, justice, tolerance, and peace for all creation. In multicultural societies such as Iraq, where diverse ethnic, religious, and cultural groups coexist, the implementation of Islamic values of Rahmatan lil ‘Alamin becomes highly important for maintaining social harmony, national unity, and peaceful coexistence. This study aims to analyze the implementation of Islamic values of Rahmatan lil ‘Alamin in multicultural life in Iraq and examine their relevance in addressing social conflict, sectarian tension, and cultural diversity within contemporary society. The research employs a qualitative descriptive approach through literature review and contextual analysis of Islamic teachings, multiculturalism, and social conditions in Iraq. The findings indicate that Islamic values emphasizing compassion, justice, tolerance, moderation, and social solidarity contribute positively to strengthening peaceful intercommunal relations and promoting social cohesion in multicultural environments. However, the implementation of these values faces challenges related to sectarian conflict, political instability, extremism, social polarization, and historical tensions among communities. The study emphasizes that strengthening inclusive Islamic education, interfaith dialogue, ethical leadership, and community cooperation is essential for promoting the values of Rahmatan lil ‘Alamin within Iraqi society. Therefore, revitalizing Islamic humanitarian values can contribute significantly to peacebuilding, reconciliation, and sustainable social harmony in multicultural national life.